Quality of life of female physicians aged 45-55 years - Gojdź, Krzysztof; Bąk-Sosnowska, Monika; Kołodziej, Sebastian; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Health is a value that has the strongest impact on the living situation of the Poles. It is often equated with good quality of life. Aim of the study: To assess the subjective sense of health of Polish female physicians in the perimenopausal age range and to examine the impact of selected sociodemographic and lifestyle-related variables on the subjective sense of health. Materials and methods : The study involved 221 working female physicians certified in a specialty. Median age was 50.57 ±2.97 years. The Subjective Health Profile (SHP) instrument and a self-developed questionnaire were used. Results : Most of respondents reported health-enhancing behaviours, as well as good physical, mental and social functioning. The study demonstrated a statistically significant relationship between the global subjective sense of health and: having children, frequency of physical activity, satisfaction with physical appearance, regularity of eating meals, mood and suicidal thoughts. Conclusions : Polish female physicians in the age range of 45-55 years have a subjective sense of good health status which is favoured by health-enhancing behaviours and mental well-being.